Continuous Titration of Inspired Oxygen Using Oxygen Reserve Index to Decrease Oxygen Exposure During One-Lung Ventilation: A Randomized Controlled Trial. (4th March 2022) - Yang, Mikyung; Kim, Jie Ae; Ahn, Hyun Joo; Choi, Young Soo; Park, MiHye; Jeong, Heejoon; Kim, Keoungah; Lee, Nam Young
Abstract : BACKGROUND: A high fraction of inspired oxygen (Fio 2 ) is administered during one-lung ventilation (OLV). However, a high Fio 2 is not physiologic and may lead to various complications. We hypothesized that continuous titration of Fio 2 using the oxygen reserve index (ORI) reduces oxygen exposure compared to conventional management during OLV. METHODS: In this randomized, double-blinded trial, patients undergoing thoracic surgery were assigned to an ORI (n = 64) or a control group (n = 60). In the ORI group, ORI was continuously displayed using multiwavelength pulse co-oximetry (Masimo) between 0 and 1 (0, no reserve; 1, maximum reserve), and Fio 2 was titrated for a target ORI of 0.21 at 5-minute intervals during OLV. In the control group, Fio 2 was adjusted using arterial blood gas analysis measured at 15 minutes after OLV initiation. The primary end point was the time-weighted average Fio 2 during OLV. RESULTS: Overall, time-weighted average Fio 2 did not differ between the groups (control versus ORI: median [interquartile range], 0.87 [0.73–1.00] vs 0.82 [0.68–0.93]; P = .09). However, in a subgroup analysis, the ORI group reduced time-weighted average Fio 2 after pulmonary vascular ligation compared to the control group (control versus ORI: median [interquartile range], 0.75 [0.70–1.00] vs 0.72 [0.59–0.89]; P = .0261). The incidence of intraoperative hypoxia (arterial oxygen saturation [Spo 2 ] <94%; control versus ORI: 32% [19/60; 95% confidence interval (CI), 20–45] vs 19% [12/64; 95% CI, 10–31]; P = .09), and postoperative complications within the first 7 days did not differ between the groups. CONCLUSIONS: ORI-guided continuous Fio 2 titration does not reduce overall oxygen exposure during OLV.